Chińska i polska terminologia dotycząca giełdy i papierów wartościowych - Grzybek, Joanna (Investigationes Linguisticae, 2009)
This article gives basic information on the stock exchanges in China and Poland and a short description of the terminology related to securities, which is difficult to understand for translators. The language and vocabulary used in Chinese and Polish financial markets have been studied following the method of parallel texts comparison. The author shows the meaning of terms and their equivalents in Chinese and Polish. The common factor affecting the terminology of both investigated languages is the English terminology source. Due to that fact, the meaning of the borrowed terminology in Poland and China is similar or exactly the same.